THE EFFECTIVENESS OF PAPAYA LEAF EXTRACT (CARICA PAPAYA L.) AS AN ANTIAGGREGATION AGENT ON PLATELET COUNT AND PLATELET AGGREGATION: IN VITRO STUDY - Ganjar Noviar; Eem Hayati; Riski Nur Ramadhani (Journal of Vocational Health Studies, 2025)
Background: In hypertensive patients, platelet hyperaggregation may lead to acute ischemic stroke, which can increase mortality or neurological deficits. Papaya (Carica papaya L.) has potential effect to mitigate complications arising from hyperaggregation, because its effectiveness as antiplatelet aggregants. Purpose: The aim of this study was to determine the effectiveness of papaya leaf extract as an antiaggregation on platelet count and platelet aggregation. Method: A quasi-experimental design was adopted observing platelet counts utilizing a hematology analyzer medonic M32 and assessing platelet aggregation values through the velaskar method. These assessments were conducted on citrated blood samples, including a control group, aspirin at 5 ppm, and a group with citrated blood augmented with papaya leaf extract at concentrations of 5 ppm, 10 ppm, and 15 ppm. Result: The platelet count in citrated blood was 186.000 cells/μL and platelet aggregation was 75%. When with aspirin at 5 ppm, the platelet count was 153.000 cells/μL and platelet aggregation was 71%. In ethanol extract from papaya leaves at 5 ppm, a platelet count of 160.750 cells/μL and platelet aggregation of 70% were exhibited. At 10 ppm, the platelet count was 149.125 cells/μL and platelet aggregation was 65%. At 15 ppm, the platelet count was 105.675 cells/μL and platelet aggregation was 56%. The results of the General Linear Model (GLM) test indicated that p (Sig.) < 0.05. Conclusion: The ethanol extract of papaya leaves can be used effectively as an antiplatelet agent, reducing both platelet count and platelet aggregation at minimum concentrations of 5 ppm and 10 ppm of papaya leaf extract.